2021
DOI: 10.3390/nu13062012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D and Newborn Telomere Length

Abstract: Nutrition is important during pregnancy for offspring health. Gestational vitamin D intake may prevent several adverse outcomes and might have an influence on offspring telomere length (TL). In this study, we want to assess the association between maternal vitamin D intake during pregnancy and newborn TL, as reflected by cord blood TL. We studied mother–child pairs enrolled in the Maternal Nutrition and Offspring’s Epigenome (MANOE) cohort, Leuven, Belgium. To calculate the dietary vitamin D intake, 108 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…As expected, our study confirmed that maternal telomeres are generally shorter than neonatal telomeres, consistent with previous research findings [16]. We also found a strong positive correlation between maternal and neonatal telomere lengths, indicating that mothers with longer telomeres gave birth to offspring with longer TL, as reported by Daneels and colleagues [17]. This suggests a hereditary component influencing neonatal telomere length.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, our study confirmed that maternal telomeres are generally shorter than neonatal telomeres, consistent with previous research findings [16]. We also found a strong positive correlation between maternal and neonatal telomere lengths, indicating that mothers with longer telomeres gave birth to offspring with longer TL, as reported by Daneels and colleagues [17]. This suggests a hereditary component influencing neonatal telomere length.…”
Section: Discussionsupporting
confidence: 93%
“…The contradicting results of maternal vitamin D levels and their effect on offspring TL may be due to the differences in the timing of vitamin D level assessments during pregnancy. For example, Daneels et al showed the importance of maternal nutrition early in pregnancy, and in particular the first trimester, being associated with TL at birth [98]. In support of the above, another study in Switzerland showed that the effects of vitamin D are more pronounced during the earlier gestational period [139].…”
Section: Maternal Nutrition and Placental And Newborn Telomeresmentioning
confidence: 92%
“…Further studies support the protective role of maternal plasma vitamin D in maintaining the newborn's TL. In two studies included in this review, the concentration of serum vitamin D during pregnancy and maternal energy intake were positively correlated with the neonate's LTL at birth [47,98]. The pleiotropic effects of vitamin D in the organism, and especially its immunomodulatory effects, may be one mechanism by which it is protective against telomere attrition [136].…”
Section: Maternal Nutrition and Placental And Newborn Telomeresmentioning
confidence: 98%
See 1 more Smart Citation
“…Prenatal programming of TL is an interesting observation, as TL can be tracked throughout time and the ranking of TL appears to be stable over time, implying that the initial setting of newborn TL contributes significantly to TL later in life [43][44][45] . In humans, prenatal maternal stress 46 , maternal pre-pregnancy BMI 9 , paternal age 47 , maternal pro-inflammatory state 48 , ambient temperatures during pregnancy 49 and maternal vitamin D intake 50 , amongst others, are reported to influence newborn TL. A birth cohort effect, which may reflect environmental factors, has been described in sheep 6 and badgers 8 , whilst lameness during pregnancy has been shown to shorten TL in newborn dairy calves 25 .…”
mentioning
confidence: 99%